Emergence of Candida auris in Russia. Issue 4 (August 2019) - Barantsevich, N.E.; Orlova, O.E.; Shlyakhto, E.V.; Johnson, E.M.; Woodford, N.; Lass-Floerl, C.; Churkina, I.V.; Mitrokhin, S.D.; Shkoda, A.S.; Barantsevich, E.P.
Summary: This paper reports the emergence of Candida auris infections in an intensive care unit at a hospital in Moscow. Forty-nine cases were diagnosed in 2016–2017, and the risk factors and antifungal susceptibilities are described. The 30-day all-cause mortality for 19 bloodstream infections in patients who did not receive appropriate antifungal therapy was 42.1%. Phylogenetic analysis of the internal transcribed spacer and D1–D2 regions and K143R substitution in the ERG11 gene indicated that the studied C. auris strains were of South Asian origin. This first reported series of C. auris infections in Russia demonstrates the rapid dissemination of this species, and the need for international surveillance and control measures.